PENGARUH STRUKTUR KEPEMILIKAN, PROFITABILITAS, DAN STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN PROPERTY AND REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Fasridon Fasridon; Yuli Angraini (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2021)
This study aims to examine the effect of structure on ownership, profitability, and capital structure of firm value on property and real estate listed on the Indonesia Stock Exchange in 2016-2020. The sample selection technique used porpusive sampling and obtained as many as 30 Property and Real Estate Companies. The data analysis technique used panel data regression analysis using Eviews 10.0. Based on the results of partial hypothesis testing, it was found that the ownership structure had no significant effect on firm value. Profitability has a positive and significant effect on firm value. Capital structure has a positive and significant effect on firm value. Based on the hypothesis, simultaneously ownership structure, profitability and capital structure have a positive and significant effect on firm value in Property and Real Estate Companies listed on the Indonesia Stock Exchange in 2016-2020. The contribution of the independent variables of ownership structure, profitability and capital structure to the dependent variable of firm value is 0.80213 or 80%. Meanwhile, 20% is influenced by other variables outside the study. It is hoped that this research can help properties and real estate listed on the Indonesia Stock Exchange to increase firm value by considering factors that have a significant effect on profitability such as ownership structure, profitability, and capital structure.